2011
DOI: 10.1097/dbp.0b013e318218d9f2
|View full text |Cite
|
Sign up to set email alerts
|

Are There Effects of Intrauterine Cocaine Exposure on Delinquency During Early Adolescence? A Preliminary Report

Abstract: Objective To ascertain whether level of intrauterine cocaine exposure (IUCE) is associated with early adolescent delinquent behavior, after accounting for prenatal exposures to other psychoactive substances and relevant psychosocial factors. Methods Ninety-three early adolescents (12.5–14.5 years old) participating since birth in a longitudinal study of IUCE reported delinquent acts via an audio computer assisted self interview (ACASI). Level of IUCE and exposure to cigarettes, alcohol, and marijuana were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 42 publications
1
19
1
Order By: Relevance
“…Others have also reported that PCE is associated with child or adolescent behavior problems, particularly externalizing behaviors such as aggression and delinquency (Bada et al, 2011, 2012; Bennett et al, 2007, 2013; Delaney-Black et al, 2000; Fisher et al, 2011; McLaughlin et al, 2011; Min, Minnes, Lang et al, 2014; Min, Minnes, Yoon et al, 2014; Minnes et al, 2010; Nordstrom Bailey et al, 2005; Sood et al, 2005; Whitaker et al, 2011). However, not all reports have confirmed these findings (Accornero et al, 2002, 2006; Allen et al, 2014; Bada et al, 2008; Bennett et al, 2002; Bridgett et al, 2011; Gerteis et al, 2011; Greenwald et al, 2011; Linares et al, 2006; Savage et al, 2005; Warner, Behnke, Hou et al, 2006). This is an important domain to investigate because adolescent behavior problems predict poorer outcomes in adulthood, including substance abuse, risky sex, psychiatric disorders, and less successful adjustment (Doherty et al, 2008; Fergusson et al, 2007; Ramrakha et al, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…Others have also reported that PCE is associated with child or adolescent behavior problems, particularly externalizing behaviors such as aggression and delinquency (Bada et al, 2011, 2012; Bennett et al, 2007, 2013; Delaney-Black et al, 2000; Fisher et al, 2011; McLaughlin et al, 2011; Min, Minnes, Lang et al, 2014; Min, Minnes, Yoon et al, 2014; Minnes et al, 2010; Nordstrom Bailey et al, 2005; Sood et al, 2005; Whitaker et al, 2011). However, not all reports have confirmed these findings (Accornero et al, 2002, 2006; Allen et al, 2014; Bada et al, 2008; Bennett et al, 2002; Bridgett et al, 2011; Gerteis et al, 2011; Greenwald et al, 2011; Linares et al, 2006; Savage et al, 2005; Warner, Behnke, Hou et al, 2006). This is an important domain to investigate because adolescent behavior problems predict poorer outcomes in adulthood, including substance abuse, risky sex, psychiatric disorders, and less successful adjustment (Doherty et al, 2008; Fergusson et al, 2007; Ramrakha et al, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…20 Another found that PCE, together with current caregiver cocaine use, caregiver negativity, community violence exposure, and prenatal tobacco exposure, was associated with adolescent cocaine use 18 ; another reported associations between heavy prenatal tobacco exposure (but not PCE) and violence, with delinquent behaviors. 46 Five studies found that postnatal caregiver drug use/drugs in the home 18,[20][21][22]32 and caregiver psychiatric/depressive symptoms [18][19][20]22,32 were associated with adolescent behavior problems. Another study found an association between community violence and peer victimization.…”
Section: Covariatesmentioning
confidence: 99%
“…Eight studies examined externalizing/ internalizing behaviors, [19][20][21][22][23]34,35,46 with mixed findings ( (1) is not mentioned, (2) is reported only as percentages of how many participants were exposed to that drug, or (3) is reported only as differences in each exposure between prenatally cocaine exposed and nonexposed groups. "Yes" indicates (1) authors examined the exposures as potential covariates but exposures did not meet their own criteria for inclusion in their models or (2) authors included them as covariates in models.…”
Section: Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Such deviant behaviors are often most prevalent in males, both cocaine-exposed and nonexposed (911, 15). Follow-up studies of preadolescents and adolescents with PCE have also reported evidence that other factors—prenatal and postnatal nicotine exposure (13, 15), childhood exposure to violence (9, 1213), ongoing caregiver substance use (4), and association with violent peers (9)—are associated with self-reported delinquent behavior. In addition, deficits in inhibitory control among children with PCE have been observed in recent research suggesting that exposed youth may be at increased risk of developing subsequent behavioral problems in part due to difficulties in regulating attention and impulsivity (16–18).…”
mentioning
confidence: 99%